“F*ck it! Let’s get to drinking – poison our livers!”: a thematic analysis of alcohol content in contemporary YouTube music videos - Cranwell, Joanne; Britton, John; Bains, Manpreet (Springer, 2016)
Purpose: To describe the portrayal of alcohol content in popular YouTube music videos.